Kurdish Alevis and the case of Dersim: historical and contemporary insights - Gezik, Erdal; Gültekin, Ahmet Kerim (Kurdish Societies, Politics, and International Relations, 2019)
The Kurdish Alevis has only recently attracted the attention of the international world. This volume achieves an understanding of the history and the contemporary situation of the Kurdish Alevis and the particular conditions where it is associated with the Kurdish identity, Alevi religion, and the history of Turkey.